2013
DOI: 10.1186/1756-3305-6-237
|View full text |Cite
|
Sign up to set email alerts
|

Development of an in vitro drug sensitivity assay based on newly excysted larvae of Echinostoma caproni

Abstract: BackgroundEchinostomiasis is one of the major food-borne trematodiases and the species Echinostoma caproni serves as a useful model for trematocidal drug discovery. The current in vitro drug sensitivity assay uses adult E. caproni worms that are incubated with candidate drugs and scored microscopically for viability at 72 hrs. The aim of this study was to investigate the use of newly excysted larvae (NEL) of E. caproni for in vitro drug testing, which would be faster, more cost effective and more ethical compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…With widespread drug resistance now affecting the control of a large range of parasitic and infectious diseases [75,76], reliance on a single drug compound raises the risk of untreatable isolates emerging, and is never good policy for sustainable parasite control. Future research may focus on the identification of novel compounds with efficacy against both juvenile and mature rumen fluke (or repositioning of existing drugs) and the selection and validation of new drug targets, using in vitro assays to assess anthelmintic efficacy against measurements such as fluke motility [77] or egg viability [78].…”
Section: Research Priorities: Playing Catch-upmentioning
confidence: 99%
“…With widespread drug resistance now affecting the control of a large range of parasitic and infectious diseases [75,76], reliance on a single drug compound raises the risk of untreatable isolates emerging, and is never good policy for sustainable parasite control. Future research may focus on the identification of novel compounds with efficacy against both juvenile and mature rumen fluke (or repositioning of existing drugs) and the selection and validation of new drug targets, using in vitro assays to assess anthelmintic efficacy against measurements such as fluke motility [77] or egg viability [78].…”
Section: Research Priorities: Playing Catch-upmentioning
confidence: 99%
“…In addition, resazurin metabolism was not correlated with the number of metacercariae present in a particular well. These results are similar to those observed for another trematode, Echinostoma caproni (Panic et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…ATP production has been used as a measure of viability for Schistosoma mansoni (Panic et al, 2015), but had been found to be unsuccessful with metacercariae (Panic et al, 2013). In the present study, we utilized a commercial recombinant luciferase that produces light in the presence of ATP.…”
Section: Discussionmentioning
confidence: 99%
“…These authors have performed a number of in vivo (using mice as definitive host) and in vitro studies with E. caproni as the drug discovery tool. They have assessed the anthelmintic properties of different medicinal plants and compounds which have allowed them to define several drug development candidates (Keiser et al, 2006a, b, c;Saric et al, 2008;Keiser 2010;Ferreira et al, 2011;Kirchhofer et al, 2011;Panic et al, 2013). Moreover, these workers have started the study of metabonomics in helminth infections using E. caproni as an experimental model (Saric et al, 2008).…”
Section: Late 20 Th Century and Early 21 Th Centurymentioning
confidence: 99%